2022
DOI: 10.3389/fmed.2022.1071409
|View full text |Cite
|
Sign up to set email alerts
|

Using exergame-based exercise to prevent and postpone the loss of muscle mass, muscle strength, cognition, and functional performance among elders in rural long-term care facilities: A protocol for a randomized controlled trial

Abstract: ObjectiveElderly individuals in long-term care facilities (LTCFs) have a higher prevalence of sarcopenia than those in the community. Exercise is the gold standard for preventing and treating sarcopenia. Regarding exercise, multicomponent exercises, including progressive resistance training (PRT), are beneficial. However, developing routine, structured exercise programs for the elderly in LTCFs is difficult because of a shortage of healthcare providers, particularly in rural regions. Exergame-based exercises c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…This may result in an increase in the sensitivity of mechanoreceptors and a stretching of the muscles surrounding the target knee joint, both of which increase the activation of muscle receptors. (28) Additionally, that would cause the muscle spindles' Ia afferents to become activated, increasing the knee joint's perception of position and reflex stabilization through an appropriate efferent response.…”
Section: Discussionmentioning
confidence: 99%
“…This may result in an increase in the sensitivity of mechanoreceptors and a stretching of the muscles surrounding the target knee joint, both of which increase the activation of muscle receptors. (28) Additionally, that would cause the muscle spindles' Ia afferents to become activated, increasing the knee joint's perception of position and reflex stabilization through an appropriate efferent response.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the use of the Nintendo Switch in the field of exergaming is worth exploring. Although there has been little research done on this topic so far, the device offers additional accessories that enable feedback during resistance, aerobic, and balance exercises 91 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the meta-analysis has already established that the conventional form of exercise did not have any beneficial impact on muscle mass [24,25], but the subsequent studies have indicated that teleexercise did have a good effect on this index [32,33]. Besides, as we mentioned above, there exist different types of remote devices for older people to prevent sarcopenia, such as Zoom, Skype™, email, and even self-developed app [29][30][31][32][33]. Apart from tele-exercise, the intervention for preventing sarcopenia in older population also encompasses tele-nutrition, as well as the combination of tele-exercise with telenutrition and other approaches [31,33].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chan et al [29] designed an online exercise programme via Zoom for older people with possible sarcopenia or at risk of fall. Tuan et al [30] created an intervention using Nintendo Switch RingFit Adventure to explore the clinical effectiveness of exergame-based exercise on muscle function and physical performance among older people. Indeed, certain studies have successfully obtained some results in this research area.…”
Section: Introductionmentioning
confidence: 99%